Dampak Pemanfaatan Multimedia Diam Dan Bergerak Terhadap Motivasi Belajar Siswa Di Tinjau Dari Status Sosial Ekonomi Orang Tua Siswa Kelas XI SMKN 1 Juwangi Boyolali Jawa Tengah - HEKSANCOKO, UNTUNG; , Prof. Dr. Bambang Sumarjoko, M Pd (2018)
Heksancoko, Untung. Q 100140088. The Impact of Multimedia Utilization Silent And Moves Against Student Learning Motivation Viewed From The Socio-Economic Status of Xi Class Parents Smkn 1 Juwangi Boyolali Central Java The purpose of this study was to: (1) Know the differences in the effects of silent multimedia usage and move towards student learning motivation . (2) Knowing the difference between parents 'socioeconomic level of high and low students' learning motivation (3) Knowing the interaction of the effects of silent and mobile multimedia utilization and the socioeconomic level of parents on student learning motivation. This research was conducted at SMK Negeri 1 Juwangi in the odd semester of 2016/2017 Academic Year. This type of research is quantitative research, using experimental research designs. The population in this study were students of class XI majoring in Technology and Engineering as many as 143 students while the number of samples in this study were 56 students. The results of this study indicate that: (1) There is a difference in the effect of using silent multimedia and moving towards student learning motivation, the average value of motivation in the group given silent multimedia is 116 while the group given multimedia motion is 123; (2) the results of the analysis of the tow way ANOVA test on parents' socioeconomic status variables obtained p value of 0.000 <0.05, because the significant value is less than 0.05, so Ho is rejected and Ha is accepted means there are differences in learning motivation based on the socioeconomic status of people old; (3) The results of anova tow way test analysis obtained p value of 0.613 <0.05, so Ho was accepted and Ha was rejected, meaning that there was no interaction between the effects of silent multimedia usage and moving towards the level of parents' socioeconomic status towards student learning motivation. Keywords: Multimedia, motivation, parental economic status